R- Fuzzy sets in factor space - Liu, Siyuan; Mi, Honghai; Choy, Tsangcheung (Penerbit Universiti Kebangsaan Malaysia, 2019)
Interval-valued fuzzy sets, both-branch fuzzy sets and R-Fuzzy sets are three extended forms of ordinary fuzzy sets. Compared to traditional fuzzy sets, interval-valued fuzzy sets have a stronger ability to express uncertainty because they provide more choices for the descriptions of attributes. Using both-branch fuzzy sets has solved some problems in engineering decision and engineering control. For R-Fuzzy sets, a new fuzzy system is constructed, with both-branch fuzzy sets as a special case. The resulting theorems improve the flexibility of uncertainty system models and expand the range of fuzzy system applications as well.